Whatever happened to Janie? - Cooney, Caroline B. (New York : Dell Laurel-Leaf, 1996)
The members of two families have their lives disrupted when a teenage girl who had been kidnapped twelve years earlier discovers that the people who raised her are not her biological parents.
Sequel to: The face on the milk carton.
Publisher's Weekly.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Brothers and sisters -- Fiction; Identity -- Fiction; Individuality -- Fiction; Kidnapping -- Fiction; Parent and child -- Fiction; Individuality -- Fiction; Kidnapping -- Fiction; Parent-child relationship -- Fiction; Siblings -- Fiction